Effect of NH4+ on the hydrothermal formation of calcium sulfate hemihydrate whiskers from fluorogypsum - Jianping Zhu; Qilin Wang; Zuolin Wang; Haixia Liu; Huachun Yang; Surendra P. Shah; Yadong Bian (Journal of Materials Research and Technology)
Fluorogypsum (FG), a large amount of solid waste, not only occupies a large amount of land resources, but also causes serious pollution to the surrounding environment. The preparation of calcium sulfate hemihydrate whiskers (CSHW) with high aspect ratio is an effective way to realize the high value-added utilization of FG. However, CSHW prepared by FG has some problems, such as poor crystallization effect and small aspect ratio. Therefore, In this paper, α-CSHW with high aspect ratio was prepared by hydrothermal method with (NH4)2SO4 as additive, and the effect of NH4+ on the microstructure, composition and crystallization behavior of α-CSHW was revealed. The mechanism was studied by XRD, SEM, FTIR, TG-DSC and molecular dynamics simulation. The results showed that the optimum content of (NH4)2SO4 was 0.5 wt%, and the aspect ratio of α-CSHW was 95.83, which was 79.12% higher than that of the blank sample. NH4+ promoted the growth of α-CSHW along the c-axis. With the increase of (NH4)2SO4 content, the promoting effect of calcium sulfate hemihydrate (CSH) crystal growth along the c-axis direction is weakened. NH4+ preferentially adsorbs on the (200) side surface parallel to the c-axis, which inhibits the growth of the crystal in the diameter direction, thereby increasing the average aspect ratio of the whisker. This study provides a new method for the effective utilization of FG and the regulation of α-CSHW.